Medical Management versus Surgical Decompression in lumbar Disc Herniation: outcomes Evaluation - Naz, Zarina; Shahbaz, Iqra; Shaikh, Mohammad Faheem; Eiman, Urwa; Khan, Fahim Ullah; Fatima Hashmi, Noor-ul-Huda (Indus Journal of Bioscience Research, 2025)
Lumbar disc herniation is a prevalent spinal condition that significantly impacts patients’ pain, mobility, and overall quality of life. Management strategies primarily include medical (conservative) treatment and surgical decompression, yet the comparative effectiveness of these approaches remains a critical area of clinical inquiry. This study evaluates and contrasts the outcomes of medical management versus surgical decompression in patients with lumbar disc herniation, focusing on pain relief, functional recovery, and quality of life improvements. A quantitative research design was employed, analyzing clinical data from 200 patients stratified into conservative and surgical treatment groups. Outcome measures included pain scores, Oswestry Disability Index (ODI), range of motion, and patient-reported quality of life assessments over a six-month follow-up period. Results indicated that while both treatment modalities provided significant symptom relief, surgical decompression demonstrated faster improvement in pain reduction and functional recovery, particularly in patients with severe neurological deficits. Conversely, medical management proved effective for patients with mild to moderate symptoms, offering satisfactory functional outcomes without surgical risks. The study also identified patient-specific factors, including age, comorbidities, and baseline disability that influenced treatment responsiveness. These findings highlight the importance of individualized treatment planning and provide evidence for optimizing therapeutic decision-making in lumbar disc herniation management.